Super-hydrophobic anti-icing radome coating and preparation method thereof
By using super-hydrophobic anti-icing radome coating, which contains components such as micro-nano super-hydrophobic powder and modified fluorocarbon resin, it solves the problems of poor adhesion and icing in the existing technology and achieves high adhesion and scratch resistance. and superhydrophobic coating with excellent self-cleaning properties, suitable for maintenance within a short time window.
Patent Information
- Application Number
- CN202410943419.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-15
AI Technical Summary
In the prior art, superhydrophobic materials have poor adhesion, easy surface cracking, or require specific spraying processes, which cannot effectively solve the problem of ice covering of airport navigation antennas in winter or rainy days, especially when the shutdown and maintenance time window is small at night.
A super-hydrophobic anti-icing radome coating is used. The coating contains micro-nano super-hydrophobic powder, modified fluorocarbon resin, trifluoropropylmethylcyclotrisiloxane, solvent, curing agent and pigment. Through a simple The preparation method is spraying on the radome to form a super hydrophobic coating with a contact angle between the surface and water greater than 150°.
The super hydrophobic coating achieves high adhesion, smoothness, good scratch resistance, and excellent self-cleaning function, which can significantly improve the anti-icing performance of the radome and is suitable for maintenance within a short time window.
Smart Images

Figure CN119331473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of radome coating materials, and in particular to a super-hydrophobic anti-icing radome coating and a preparation method thereof. Background Art
[0002] In modern air traffic control, radar control is an important control method for modern controllers. Multiple coverage of radars is needed to solve the problem of signal stability and continuity in radar control. Radar stations need to be built in different regions to solve the problem of radar coverage. In winter or rainy days, the surface of the radar cover of these radar stations may be covered with ice or rain film. At this time, the working efficiency of the antenna will be significantly reduced, the coverage area will be reduced, and the noise temperature will increase, thereby affecting the quality of communication signals. In order to improve the stability of radar operation and ensure civil aviation safety, it is very necessary to improve the anti-icing performance of the antenna cover. Due to historical reasons, most of the antenna covers used in some navigation and supporting antenna products in my country did not consider the impact of icing during the manufacturing process. After years of use, the antenna covers of some antennas have aged or corroded seriously. In particular, antennas deployed in freezing environments are greatly affected by icing, and necessary maintenance is urgently needed to extend their service life and ensure the safety of civil aviation operations.
[0003] Patent No. 202211130260 discloses a super-hydrophobic glass microbead and a preparation method thereof and a super-hydrophobic coating and a preparation method thereof. The coating prepared by this method has been tested and its electrical performance test data exceeds the technical indicators of the antenna cover and cannot be used.
[0004] Although many studies have shown that superhydrophobic coatings have good anti-icing properties, most of them have poor coating adhesion, or the powders used are insulating but their electrical properties do not meet the technical indicators of the antenna cover, which requires further research. Summary of the invention
[0005] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to overcome the problems in the prior art such as poor adhesion of super-hydrophobic materials, easy surface cracking or the need for a specific spraying process, solve the problems such as the small time window for nighttime maintenance of airport navigation antennas, and provide a super-hydrophobic anti-icing antenna cover coating and a preparation method thereof.
[0006] The preparation process of this method is simple and can be industrially scaled up. The obtained super-hydrophobic anti-icing radome coating is sprayed on the radome to quickly obtain a super-hydrophobic coating with a surface contact angle with water greater than 150°, and the coating surface is flat and smooth with good scratch resistance.
[0007] Technical solution:
[0008] In order to achieve the above object, the present invention provides a super hydrophobic anti-icing radome coating, wherein the super hydrophobic anti-icing radome coating comprises micro-nano super hydrophobic powder, modified fluorocarbon resin, trifluoropropylmethylcyclotrisiloxane, solvent, curing agent and pigment;
[0009] The micro-nano super-hydrophobic powder is prepared by the following steps: dispersing inorganic micro-nano powder in a mixed solvent, then adding a water-oil dual-repellent treatment agent and triethylamine for mixed contact, and finally fractionating, washing, drying, grinding, and high-temperature curing to obtain a nano super-hydrophobic powder;
[0010] The modified fluorocarbon resin is prepared by polymerizing quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide;
[0011] The quaternary ammonium salt fluorinated acrylate has a structure as shown in the following formula A:
[0012]
[0013] Furthermore, the solvent is butyl acetate.
[0014] Furthermore, the modified fluorocarbon resin is prepared by the following steps:
[0015] (1) Adding dimethylaminoethyl acrylate, perfluorohexyl propylene oxide, sodium hydroxide and anhydrous ethanol into a reactor, heating to 50-60° C. and reflux reacting for 3-4 hours, cooling and crystallizing, filtering and drying to obtain a quaternary ammonium salt fluorinated acrylate;
[0016] (2) In a reactor, add quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide, heat to 70-80° C., add an initiator and react for 3-4 hours, cool, filter and dry to obtain the modified fluorocarbon resin.
[0017] Furthermore, in the step (1), the mass ratio of dimethylaminoethyl acrylate, perfluorohexylpropylene oxide and sodium hydroxide is (6-8): (18-21): (2-3);
[0018] In the step (2), the initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile;
[0019] In the step (2), the mass ratio of the quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide is (6-8): (3-5): (2-4).
[0020] Furthermore, the inorganic micro-nano powder is selected from at least one of nano-silicon dioxide, pretreated boron nitride powder or potassium titanate whiskers;
[0021] The water-oil amphiphobic treatment agent is selected from at least one of tetraethoxysilane, fluoroalkyltrimethoxysilane or fluoroalkyltriethoxysilane;
[0022] The mass ratio of the inorganic micro-nano powder, the water-oil amphiphobic treatment agent and triethylamine is 1:(0.4-1.0):(0.1-0.3).
[0023] Furthermore, the particle size of the nano-silicon dioxide is 10-300 nm; the particle size of the pretreated boron nitride powder is 0.1-10 μm; the potassium titanate whisker is an insulating potassium titanate whisker;
[0024] The pretreated boron nitride powder is prepared by ball milling the boron nitride at a rotation speed of 80-120 r / min for 20-24 hours;
[0025] The mixed solvent is prepared by mixing an organic solvent with water, and the organic solvent is selected from at least one of ethanol and isopropanol.
[0026] Furthermore, the inorganic micro-nano powder comprises nano silicon dioxide, pretreated boron nitride powder and potassium titanate whiskers in a mass ratio of (0.8-1.2):(1.8-2.2):(0.1-0.3).
[0027] When the amount of nano-silica exceeds the upper limit, the risk of cracking on the coating surface increases and the adhesion decreases; when the amount of nano-silica exceeds the lower limit, the risk of cracking on the coating surface decreases, but the rolling angle of water droplets increases, affecting the hydrophobic performance; when the amount of nano-potassium titanate whiskers exceeds the upper limit, the coating surface will be rougher, the adhesion will decrease, and the rolling angle of water droplets will increase, affecting the hydrophobic performance; when the amount of nano-potassium titanate whiskers exceeds the lower limit, the risk of cracking on the coating surface increases.
[0028] Furthermore, the super-hydrophobic anti-icing radome coating also contains perfluorosilane and a fluorine-containing surfactant.
[0029] Furthermore, the super hydrophobic anti-icing radome coating comprises, by weight, 2-4 parts of micro-nano super hydrophobic powder, 2-6 parts of modified fluorocarbon resin, 0.1-0.6 parts of trifluoropropylmethylcyclotrisiloxane, 0.1-0.6 parts of perfluorosilane, 0.1-0.6 parts of fluorine-containing surfactant, 15-25 parts of solvent, 0.5-1.2 parts of curing agent and 0.1-0.8 parts of pigment.
[0030] Furthermore, in the preparation of the micro-nano super-hydrophobic powder, the temperature of the mixed contact is 20-60° C., and the time of the mixed contact is 1-15 hours; the temperature of the high-temperature curing is greater than 140° C., and the time is greater than 10 minutes.
[0031] The method for preparing any one of the above-mentioned super-hydrophobic anti-icing radome coatings comprises the following steps:
[0032] (1) dispersing a micro-nano super-hydrophobic powder in a solvent, and then adding a modified fluorocarbon resin, trifluoropropylmethylcyclotrisiloxane, perfluorosilane and a fluorine-containing surfactant to mix to obtain a mixed solution;
[0033] (2) Adding a curing agent and a pigment into the mixed liquid to prepare the super-hydrophobic anti-icing antenna cover coating.
[0034] Beneficial effects:
[0035] 1. The super-hydrophobic composite powder in the present invention adopts industrialized boron nitride, potassium titanate whisker, silicon dioxide, and pigment as raw materials, which can not only save the formulation cost, but also form the lotus leaf effect of the super-hydrophobic material after coating treatment; the super-hydrophobic composite powder is applied to prepare a super-hydrophobic coating, and the super-hydrophobic coating obtained by coating finally has excellent super-hydrophobic performance, and the contact angle between the surface of the super-hydrophobic coating and water is greater than 150°, and the super-hydrophobic coating has a good self-cleaning function.
[0036] 2. The boron nitride powder used in the present invention has good insulation and thermal conductivity, excellent electrical performance indicators, and a relatively fast ice melting speed, which can greatly improve the ability of navigation equipment to cope with extreme climates.
[0037] 3. In the present invention, the modified fluorocarbon resin prepared by copolymerization of quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide is added. On the one hand, by polymerizing the quaternary ammonium salt fluorinated acrylate in the resin structure, the fluorine-containing group thereof can not only significantly improve the hydrophobicity of the prepared coating, but also enhance the weather resistance of the coating and expand the scope of application; on the other hand, the quaternary ammonium structure in the quaternary ammonium salt fluorinated acrylate can further improve the surface activity of the fluorocarbon resin, thereby improving the hydrophobicity of the prepared coating.
[0038] 4. The super-hydrophobic coating prepared by the method described in the present invention is finally cured to obtain a super-hydrophobic coating. In addition to having excellent super-hydrophobic performance, it also has excellent wear resistance and scratch resistance. The super-hydrophobic performance of the coating before and after polishing and scratching is not affected, and the super-hydrophobic performance of the coating is very stable.
[0039] 5. The anti-icing coating of the present invention has a simple construction process and can quickly achieve super-hydrophobic performance, which is suitable for the short maintenance window of airport navigation equipment.
[0040] 6. The preparation method of the present invention is simple and easy, does not require high temperature and high pressure and multi-step reactions, and the raw materials are cheap and easily available, can be industrially scaled up, and has great industrial prospects. The super-hydrophobic coating obtained after the industrial scale-up experiment still has good super-hydrophobic properties, successfully overcoming the defects existing in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a block diagram of the electrical performance test system for the antenna cover unit.
[0042] Figure 2 FIG. 4 is a curve showing the insertion loss versus frequency of the material of the embodiment of the present invention.
[0043] Figure 3 The insertion loss curve of the comparative material of the present invention is plotted against the frequency.
[0044] Figure 4 This is the insertion loss curve of the honeycomb panel material versus frequency.
[0045] Figure 5 This is a rain test picture.
[0046] Figure 6 and Figure 7 This is a test chart of the hydrophobic performance of the example material after xenon lamp aging.
[0047] Figure 8 and Fig. 9 This is a test diagram of the anti-icing performance of the material of the present invention.
[0048] Figure 5 , Figure 8 , Fig. 9 The “test sample M750-M5# anti-icing super-hydrophobic coating” is the anti-icing super-hydrophobic coating sample in the embodiment of the present application, and the “comparison sample fluorocarbon coating” is the product of the comparative example of the present application. DETAILED DESCRIPTION
[0049] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0050] The perfluorosilane is heptadecafluorodecyltrimethoxysilane; the fluorine-containing surfactant is sodium perfluorononenyloxybenzenesulfonate; the curing agent is ethylenediamine; the pigment is nano titanium dioxide; and the remaining reagents and equipment are conventional reagents and equipment in the technical field.
[0051] Preparation of modified fluorocarbon resin
[0052] The modified fluorocarbon resin is prepared by the following steps:
[0053] (1) In a 250 mL four-necked flask equipped with a spherical condenser, a mechanical stirrer, a thermometer and a hollow stopper, 0.3 g of dimethylaminoethyl acrylate, 0.9 g of perfluorohexyl propylene oxide, 0.1 g of sodium hydroxide and 50 mL of anhydrous ethanol were added, heated to 60° C. and refluxed for 4 hours, cooled and crystallized, filtered and dried to obtain a quaternary ammonium salt fluorinated acrylate;
[0054] (2) In a reactor, 3 g of quaternary ammonium salt fluorinated acrylate, 2 g of methyl methacrylate and 1 g of methacrylamide were added, heated to 75° C., 0.1 g of azobisisobutyronitrile was added and reacted for 3 hours, and the modified fluorocarbon resin was obtained after cooling, filtering and drying.
[0055] Example
[0056] 1. Prepare micro-nano super hydrophobic powder by the following steps:
[0057] By weight, 1 part of inorganic micro-nano powder is dispersed in 20 parts of a mixed solvent, and then 0.5 parts of fluorinated alkyl trimethoxysilane and 0.2 parts of triethylamine are added and mixed at 50° C. for 3 hours, and finally fractionated, washed, dried, ground, and cured at 200° C. for 20 minutes to obtain a nano super hydrophobic powder;
[0058] The inorganic micro-nano powder includes nano silicon dioxide with a particle size of 15 nm, pretreated boron nitride powder with a particle size of 500 nm, and potassium titanate whiskers in a mass ratio of 1:2:0.2;
[0059] The pretreated boron nitride powder is prepared by ball milling the boron nitride at a rotation speed of 100 r / min for 24 hours;
[0060] The mixed solvent includes isopropanol, ethanol and water in a mass ratio of 15:0.1:1.
[0061] 2. Prepare a super-hydrophobic anti-icing radome coating by the following steps: by weight,
[0062] (1) dispersing 3 parts of micro-nano super hydrophobic powder in 20 parts of butyl acetate, and then adding 5 parts of modified fluorocarbon resin, 0.3 parts of trifluoropropylmethylcyclotrisiloxane, 0.3 parts of perfluorosilane and 0.25 parts of fluorine-containing surfactant to obtain a mixed solution;
[0063] (2) 0.7 parts of curing agent and 0.7 parts of pigment are added to the mixed solution to prepare the super hydrophobic anti-icing antenna cover coating.
[0064] Comparative Example
[0065] The coating was prepared by the following steps: by weight,
[0066] (1) dispersing 3 parts of glass microspheres in 10 parts of butyl acetate, 15 parts of ethanol and 1 part of water, and then adding 1 part of perfluorosilane, 3 parts of triethylamine and 3.5 parts of epoxy resin to mix to obtain a mixed solution;
[0067] (2) 0.7 parts of a curing agent was added to the mixed solution to prepare the coating.
[0068] Performance Testing
[0069] 1. Electrical performance test:
[0070] In a microwave darkroom, a vector network analyzer (model: MS46322A) and a double-ridged horn antenna (model: HD-10180DRHA10S) were used to Figure 1 Connect the antenna test system as shown and power it on for preheating. The test auxiliary antenna is used for transmission, and the antenna under test is used for reception. The distance between the two antennas meets the antenna far-field test requirements, that is, d>2D 2 / λ, d is the distance between the transmitting and receiving antennas, D is the aperture of the antenna under test, λ is the working wavelength, and the two antennas are installed at the same height with the same polarization.
[0071] The speaker model is HD-10180DRHA10S, the operating frequency is 1~18GHz, the gain is 7~13dB, the beam width is 30~80°, the aperture size is 284mm*160mm. According to the actual test environment and far-field test conditions, the distance d between the transmitting and receiving antennas is 5 meters, and the height of the speaker is 1 meter from the ground.
[0072] Select the network analyzer working mode as the sweep test mode, set the target test parameter to the S21 amplitude, that is, port 1 transmits the signal and port 2 receives the signal; set the starting frequency f START and the stop frequency f STOP , the operating frequency of the antenna cover unit under test is [f1, f2], and f is set START <f1,f STOP >f2. After the instrument status setting is completed and the system is in a stable state, perform system calibration, that is, store the received sweep test data into the instrument register. While keeping all the settings of the instrument unchanged, place the antenna cover unit under test between the transmitting and receiving antennas, and close to the receiving antenna, with a distance of 0.5 to 1m from the receiving antenna (adjust the position within this range to reduce the spatial standing waves caused by the antenna cover unit). Note: The initial position of the antenna cannot be moved when setting up the antenna cover unit. Compare the test data after adding the antenna cover unit with the data in the register (the instrument has this function, which is completed automatically). The amplitude curve (in dB) obtained by comparison is the insertion loss curve of the antenna cover unit with the frequency.
[0073] After testing, the insertion loss curve of the embodiment material versus frequency is as follows: Figure 2 The insertion loss curve of the comparative material is as follows: Figure 3 The insertion loss curve of honeycomb panel material is as follows: Figure 4 ;
[0074] The electrical performance index test statistics are as follows:
[0075]
[0076] 2. Rain test:
[0077] Rain test results are as follows Figure 5 After the rain test, the anti-icing super-hydrophobic coating sample in the embodiment of the present invention has good hydrophobicity, and no water film is formed on the coating surface; while a large amount of water droplets accumulate on the surface of the comparative material.
[0078] 3. Dielectric constant test:
[0079] According to SGS testing, the dielectric constant of the anti-icing super-hydrophobic coating sample in the embodiment of the present invention is about 3.83.
[0080] 4. Aging performance test:
[0081] like Figure 6 and Figure 7 As shown, after the anti-icing super-hydrophobic coating sample in the embodiment was subjected to a xenon lamp aging test for 500 hours, the coating still had good super-hydrophobic properties.
[0082] 5. Anti-icing and ice melting test:
[0083] Place the surface sprayed with the anti-icing coating in a constant temperature freezer for more than 24 hours, then spray a water-ice mixture with a temperature close to 0°C onto the coating surface, and observe and record the icing conditions.
[0084] like Figure 8 and Fig. 9 As shown, at -10°C, the anti-icing super-hydrophobic coating of the present invention reduces the amount of ice by about 80% compared with the conventional polytetrafluoroethylene coating, and the ice melting speed is about 10 minutes faster; however, at a low temperature of -20°C, the formation speed of ice crystals is accelerated, and the anti-icing ability is not outstanding.
[0085] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A super-hydrophobic anti-icing radome coating, characterized in that: The super-hydrophobic anti-icing radome coating comprises micro-nano super-hydrophobic powder, modified fluorocarbon resin, trifluoropropylmethylcyclotrisiloxane, solvent, curing agent and pigment; The micro-nano super-hydrophobic powder is prepared by the following steps: dispersing inorganic micro-nano powder in a mixed solvent, then adding a water-oil dual-repellent treatment agent and triethylamine for mixed contact, and finally fractionating, washing, drying, grinding, and high-temperature curing to obtain a nano super-hydrophobic powder; The modified fluorocarbon resin is prepared by polymerizing quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide; The quaternary ammonium salt fluorinated acrylate has a structure as shown in the following formula A: 。 2. The super-hydrophobic anti-icing radome coating according to claim 1, characterized in that: The modified fluorocarbon resin is prepared by the following steps: (1) Add dimethylaminoethyl acrylate, perfluorohexyl propylene oxide, sodium hydroxide and anhydrous ethanol into a reactor, heat to 50-60°C for reflux reaction for 3-4 hours, cool and crystallize, filter and dry to obtain quaternary ammonium salt fluorinated acrylate; (2) In a reactor, add quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide, heat to 70-80° C., add an initiator and react for 3-4 hours, cool, filter and dry to obtain the modified fluorocarbon resin.
3. The super-hydrophobic anti-icing radome coating according to claim 2, characterized in that: In the step (1), the mass ratio of dimethylaminoethyl acrylate, perfluorohexylpropylene oxide and sodium hydroxide is (6-8): (18-21): (2-3); In step (2), the initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile; In the step (2), the mass ratio of the quaternary ammonium salt fluorinated acrylate, methyl methacrylate and methacrylamide is (6-8): (3-5): (2-4).
4. The super-hydrophobic anti-icing radome coating according to claim 1, characterized in that: The inorganic micro-nano powder is selected from at least one of nano silicon dioxide, pretreated boron nitride powder or potassium titanate whiskers; The water-oil amphiphobic treatment agent is selected from at least one of tetraethoxysilane, fluoroalkyltrimethoxysilane or fluoroalkyltriethoxysilane; The mass ratio of the inorganic micro-nano powder, the water-oil amphiphobic treatment agent and triethylamine is 1: (0.4-1.0): (0.1-0.3).
5. The super-hydrophobic anti-icing radome coating according to claim 4, characterized in that: The particle size of the nano silicon dioxide is 10-300nm; the particle size of the pretreated boron nitride powder is 0.1-10μm; the potassium titanate whisker is an insulating potassium titanate whisker; The pretreated boron nitride powder is prepared by ball milling the boron nitride at a rotation speed of 80-120 r / min for 20-24 hours; The mixed solvent is prepared by mixing an organic solvent with water, and the organic solvent is selected from at least one of ethanol and isopropanol.
6. The super-hydrophobic anti-icing radome coating according to claim 4, characterized in that: The inorganic micro-nano powder comprises nano silicon dioxide, pretreated boron nitride powder and potassium titanate whisker in a mass ratio of (0.8-1.2): (1.8-2.2): (0.1-0.3).
7. The super-hydrophobic anti-icing radome coating according to claim 1, characterized in that: The super-hydrophobic anti-icing radome coating further comprises perfluorosilane and a fluorinated surfactant.
8. The super-hydrophobic anti-icing radome coating according to claim 7, characterized in that: In parts by weight, the super-hydrophobic anti-icing radome coating comprises 2-4 parts of micro-nano super-hydrophobic powder, 2-6 parts of modified fluorocarbon resin, 0.1-0.6 parts of trifluoropropylmethylcyclotrisiloxane, 0.1-0.6 parts of perfluorosilane, 0.1-0.6 parts of fluorine-containing surfactant, 15-25 parts of solvent, 0.5-1.2 parts of curing agent and 0.1-0.8 parts of pigment.
9. The super-hydrophobic anti-icing radome coating according to claim 1, characterized in that: In the preparation of the micro-nano super-hydrophobic powder, the temperature of the mixed contact is 20-60° C., and the time of the mixed contact is 1-15 hours; the temperature of the high-temperature curing is greater than 140° C., and the time is greater than 10 minutes.
10. The method for preparing the super hydrophobic anti-icing radome coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) dispersing micro-nano super-hydrophobic powder in a solvent, and then adding modified fluorocarbon resin, trifluoropropylmethylcyclotrisiloxane, perfluorosilane and fluorine-containing surfactant to obtain a mixed solution; (2) Adding a curing agent and a pigment into the mixed liquid to prepare the super-hydrophobic anti-icing antenna cover coating.
Citation Information
Patent Citations
UV-light curing paint
CN106381020A
Preparation method of photosensitive antibacterial silicon dioxide pellets and application of photosensitive antibacterial silicon dioxide pellets
CN107114366A
Super-hydrophobic coating for ship-borne radar radome and preparation method of super-hydrophobic coating
CN117363167A
Process for the preparation of fluorinated quaternary ammonium salts
WO2009075561A2